Program Act Your Movement in Physics berbasis Praktikum Sederhana di MTS YPI Darul Huda OKU Timur - Arini Rosa Sinensis; Thoha Firdaus; Widayanti Widayanti; Effendi Effendi; Siti Anisatur Rofiqah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2021)
The Act Your Movement in Physics (AYMP) program is an action and real action for the Physics Education study program at Nurul Huda University to contribute in the fields of education, community empowerment and the environment. This AYMP activity carried out is in the field of Education and learning, namely conducting demonstration activities and Physics Practicum in schools, namely at MTS YPI DARUL HUDA. The implementation method for this service activity is preparation, implementation and evaluation. In the preparation stage, namely preparing basic physics practicum tools, namely, caliper, microscope and screw micrometer. The implementation stage is to provide learning with the demonstration method to students followed by direct practicum activities by students. In the evaluation phase, students and teachers are asked to respond to the activities that have been carried out. The result of this service is the establishment of cooperation with schools in the field of science learning activities, teachers are very helpful and students are very enthusiastic and motivated to study science more actively